2018
DOI: 10.1029/2018jc014074
|View full text |Cite
|
Sign up to set email alerts
|

North Atlantic Ocean Internal Decadal Variability: Role of the Mean State and Ocean‐Atmosphere Coupling

Abstract: The origin of the decadal variability in the North Atlantic Ocean is investigated in a series of coupled and ocean‐only numerical experiments. Two versions of the IPSL‐CM5A model are considered, differing only by their atmospheric horizontal resolution (3.75° × 1.87° and 2.5° × 1.25°). When the ocean model is forced by the climatological surface fluxes from the low atmospheric resolution coupled model version, a 20‐year variability emerges, similar to the variability found in the coupled simulation. Such decad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 66 publications
(122 reference statements)
4
32
0
Order By: Relevance
“…This low-frequency variability in the MOC is consistent with several other ocean hindcast studies (e.g., Biastoch et al 2008;Robson et al 2012;Danabasoglu et al 2016). Such a MOC variability with ;20-yr periodicity may be intrinsic ocean only mode related to deep-water formation at high latitudes (e.g., Kwon and Frankignoul 2014), which can be intensified by the atmospheric forcing (Gastineau et al 2018). We note that these low-frequency MOC changes are beyond the scope of this paper because of the limited length of model data used.…”
Section: Moc and Its Variabilitymentioning
confidence: 90%
“…This low-frequency variability in the MOC is consistent with several other ocean hindcast studies (e.g., Biastoch et al 2008;Robson et al 2012;Danabasoglu et al 2016). Such a MOC variability with ;20-yr periodicity may be intrinsic ocean only mode related to deep-water formation at high latitudes (e.g., Kwon and Frankignoul 2014), which can be intensified by the atmospheric forcing (Gastineau et al 2018). We note that these low-frequency MOC changes are beyond the scope of this paper because of the limited length of model data used.…”
Section: Moc and Its Variabilitymentioning
confidence: 90%
“…Such a warmer mean state modifies the subpolar gyre currents and the subsurface stratification in the Eastern Atlantic Ocean where the mixed layer is deepest in IPSL-CM5A models. These changes were suggested to explain a smaller growth of baroclinic instabilities triggering the propagation of westward propagating anomalies (Gastineau et al, 2018). It is therefore likely that the different tuning of IPSL-CM5A2 led to similar changes.…”
Section: Ocean Variabilitymentioning
confidence: 96%
“…This difference can be explained by the different tuning of the two model versions. Gastineau et al (2018) used IPSL-CM5A-MR, a variant of IPSL-CM5A with an improved horizontal resolution in the atmosphere (2.5°× 1.25°vs 3.75°× 1.87°), and also found that a warmer mean state led to a reduction of the 20-yr variability https://doi.org/10.5194/gmd-2019-332 Preprint. Discussion started: 9 December 2019 c Author(s) 2019.…”
Section: Ocean Variabilitymentioning
confidence: 99%
“…-Earth system models of intermediate complexity (Claussen et al, 2002), with coarse spatial resolution and simplifications in the physics, allow very efficient computation times and have been used extensively to explore Quaternary paleoclimates and run transient simulations (Roberts et al, 2014;Caley et al, 2014). As an example, the iLOVECLIM model (Goosse et al, 2010;Roche, 2013) provides more than 2500 simulated years per day (hereafter SYPD) on one computing core at a ∼ 5.6 • spatial resolution (three vertical levels) in the atmosphere and a full ocean general circulation model (OGCM) at 3 • × 3 • (21 vertical levels) with two tracers. Performance is still 850 SYPD with 20 tracers in the ocean (Bouttes et al, 2015b;Missiaen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%